Experimental validation of a current-source converter with reduced dc-link operating as shunt active power filter - Oliveira, Cátia Patrícia Fraga (2021)
Nowadays, the majority of electronic equipment behaves as nonlinear loads, introducing power quality problems into the power grid, namely, current harmonics and low power factor. These problems contribute to reduce the efficiency of the power grid and can cause malfunctioning of sensitive loads connected to the power grid. Therefore, it is important to develop power electronics solutions capable to mitigate these power quality problems. In this context, this paper presents a novel single-phase shunt active power filter (SAPF) based on a current-source converter, where the key differencing factor, when compared with the conventional approach, is the reduced dc-link. As the proposed topology requires a reduced dc-link, it represents a relevant advantage, requiring a less bulky inductance in the dc-link, reducing the losses, cost, and volume. The proposed SAPF with reduced dc-link is introduced in detail along the paper, and a comprehensive comparison with the conventional SAPF is established based on computer simulations. Besides, an experimental validation is carried out with a developed laboratory prototype, validating the main advantages of the proposed SAPF with reduced dc-link.